Middle and High School Teacher Responses to an Authentic Argument Writing Seminar. Issue 4 (10th September 2016) - Kohnen, Angela M.
Abstract: This qualitative study examined a five‐day summer professional development workshop for English language arts teachers on argument writing. Fourteen teacher participants learned from five different professionals who discussed the role of argument in their fields. Teacher blog posts were coded to understand what teacher participants perceived as important to or different from their previous understandings. Findings include (a) authentic argument is as much about an attitude or state of mind as it is about a product on paper; (b) in schools, argument instruction is very focused on structure; (c) research and data are essential to argument outside of schools; and (d) authentic argument has consequences. These findings have implications for those teaching argument writing as an authentic act.